“Efectos de la aplicación del producto GSI-36 como bioestimulador, enraizador sobre la semilla de arroz (oryza sativa), variedad capirona bajo condiciones de laboratorio” - Grández Chasnamote, David (2008)
The present work of investigation(research) hadas aim(lens) determine the effect of the Commercial product GSl-36, since(as,like) germinatingly and enraizador on the seed of the culture(culturing) of rice variety Capirona that way to determine the best doses of the product fer every kg. From seed to others of obtaining seeds with high degree of germination and size of roots and with this to guarantee a good development of the plántulas. This work 1 realiza in the facilities of the Regional Committee of Seeds of St Martin this located in Tarapoto's Province to a south Latitude 6°30'00 ", Length West 76 ° 29'00 "toan Altitude of 330 m.s.n.m.m. 1 apply a DCR to him(you,them) with arrangement factorial 4 x 9, with three repetitions for treatment. The variety of rice CAPIRONA was gathered of farmers' different fields inscribed(registered) in the CORESE-SM in the Commercial area. In addition the CORESE-SM 1 facilitate the work for which in his(her,your) facilities it(he,she) was possessing(relying on) stored seeds, the Commercial product GSl-36 was granted by the BIOCHEMICAL INTERNATIONAL COORPORACION CBI. In the obtained analyses they brought(reported) that the major averages of germination (normal Plántulas) were with 4 and 6 gr/Kg. of the product GSl-36. The major size of roots was obtained by 4 and 8 g. of the product to 3 and 5 months of storage of the Variety Capirona. This analysis shows us that finally that the best doses are of 4 and 6 g. of the commercial product GSl-36 for every kg. Of seed of rice Capirona from 3 to 7 months of storage